Potential of Active Compounds in Mangroves as Food Preservatives: a Literature Review - Sofia, Irnanda Ummi; Kumalasari, Ika Dyah; Osman, Noridah Binti (Sainteks, 2022)
Mangroves have an essential role in food and nutrition for the public and coastal communities. This study aimed to obtain a general description of the types of mangrove plants, their content of bioactive compounds, extraction methods, and the potential for development and processing as alternative food sources. This study was a literature review that collected articles from Google Scholar, Semantic Scholar, ScienceDirect, and Hindawi based on relevant articles. The types of mangrove plants whose fruit can be developed as food include Avicennia marina, A. alba, A. lanata, Bruguiera gymnorhiza, Sonneratia alba, and Nipah fruticans. From an economic point of view, mangroves can be used as various processed foods, beverages, and food materials.